Coherent J / ψ and ψ ′ photoproduction at midrapidity in ultra-peripheral Pb–Pb collisions at √ˢɴɴ =5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akbar, Z.; Akindinov, A.; et al. (Springer Science and Business Media Deutschland GmbH, 2021)
The coherent photoproduction of J/ψ and ψ′ mesons was measured in ultra-peripheral Pb–Pb collisions at a center-of-mass energy √ˢɴɴ = 5.02 TeV with the ALICE detector. Charmonia are detected in the central rapidity region for events where the hadronic interactions are strongly suppressed. The J/ψ is reconstructed using the dilepton (l⁺ l⁻) and proton–antiproton decay channels, while for the ψ′ the dilepton and the l⁺ l⁻ π⁺ π⁻ decay channels are studied. The analysis is based on an event sample corresponding to an integrated luminosity of about 233 μb⁻¹ . The results are compared with theoretical models for coherent J/ψ and ψ′ photoproduction. The coherent cross section is found to be in a good agreement with models incorporating moderate nuclear gluon shadowing of about 0.64 at a Bjorken- x of around 6 × 10⁻⁴, such as the EPS09 parametrization, however none of the models is able to fully describe the rapidity dependence of the coherent J/ψ cross section including ALICE measurements at forward rapidity. The ratio of ψ′ to J/ψ coherent photoproduction cross sections was also measured and found to be consistent with the one for photoproduction off protons.
Keywords: Physics; Rapidity; Luminosity; Hadron; Nuclear physics; Proton; Meson; Particle physics; Parametrization (atmospheric modeling); Energy (signal processing); Astrophysics; https://purl.org/pe-repo/ocde/ford#1.03.00